'Poor me' versus 'Bad me' paranoia: The association between self‐beliefs and the instability of persecutory ideation. (17th January 2012) - Melo, Sara Sigmaringa; Bentall, Richard P.
<x xml:space="preserve">Abstract</x> Objectives. To investigate whether different self‐attributes would be associated with different degrees of deservedness of persecution in a clinical paranoid sample. Background. Some studies have shown differences between the self‐esteem (SE) of individuals with 'Poor Me' (PM) and 'Bad Me' (BM) paranoia (Bentall ., 2009; Chadwick, Trower, Juusti‐Butler, & Maguire, 2005). Most studies investigating this relationship have employed a cross‐sectional design, precluding the investigation of changes over time. Methods. In the cross‐sectional part of the study, 45 clinical participants and 25 controls were assessed in terms of paranoia, deservedness of persecution, SE, self‐discrepancies, daily events, and coping strategies. In the longitudinal part of the study, the clinical group was re‐assessed over a period of another 2 days, in order to study changes in these variables. Results. At baseline, there were no differences between the SE of the two paranoia presentations, which was significantly lower than the controls'. However, the paired‐samples repeated analysis found the SE of individuals when in a PM presentation was higher than when they were BM. Only BM paranoia was found to be associated with higher self‐ideal:self‐actual self‐discrepancies than the other groups. The longitudinal analysis indicated that, having been PM and having low SE at the previous assessment day made it more likely that individuals would be in BM subsequently. No differences in causal attributions made for ecological events were found between the groups. Higher SE was found to be more likely when individuals coped with adversities by using social support. Conclusions. Both deservedness of persecution and self‐views appear to be unstable in individuals with paranoia and to change consistently over time, a finding which is in keeping with Bentall .'s (2001) dynamic model of paranoia.